VALUASI VEGETASI POHON RUANG TERBUKA HIJAU OBJEK WISATA RELIGI MAKAM SULTAN SURIANSYAH DI TEPIAN SUNGAI KUIN KOTA BANJARMASIN - Dienny Redha Rahmani; Hanny Maria Caesarina (Universitas Lambung Mangkurat, 2019)
The value of vegetation for the community and the environment shows by the criteria of comfort and economic values that can be estimated. Sultan Suriansyah tomb tourist area located on the Kuin riverbank has vegetation that value as shade and aesthetics. Vegetation value in this area needs to be assessed to find out its ecological and economic values. Valuation of tree vegetation is conducted in two methods, the valuation of Convenience using the Thermal Humidity Index (THI) method and the stored Carbon Valuation method. Valuation of Vegetation shows that tree vegetation in the tourist area of the tomb of Sultan Suriansyah Kuin Banjarmasin is not good enough. This is based on the value of the resilience with HTI (>26) categorized as uncomfortable. Furthermore, the average value of carbon stored per day for one tomb area is still low.